2021
DOI: 10.1186/s12966-021-01150-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of multimorbidity and its association with physical activity and sleep duration in middle aged and elderly adults: a longitudinal analysis from China

Abstract: Background Preventing chronic disease is important in health policy in countries with significantly ageing populations. This study aims to examine the prevalence of chronic disease multimorbidity and its association with physical activity and sleep duration; and to understand whether physical activity modifies associations between sleep duration and multimorbidity. Methods We utilized longitudinal data of a nationally-representative sample from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 47 publications
8
57
3
4
Order By: Relevance
“…Moreover, our result agrees with the finding of a longitudinal study in Canada which reported that chronic diseases may be influenced by disrupted sleep (46). Finally, a recent study in China (47) reported that multimorbidity and poor sleep are associated overall in both genders and also among women separately (47). However, it is not yet clear if the poor quality of sleep is a consequence of the presence of several chronic diseases in an individual or whether it leads to an increase in the number of chronic diseases in an individual.…”
Section: Current Smokersupporting
confidence: 93%
“…Moreover, our result agrees with the finding of a longitudinal study in Canada which reported that chronic diseases may be influenced by disrupted sleep (46). Finally, a recent study in China (47) reported that multimorbidity and poor sleep are associated overall in both genders and also among women separately (47). However, it is not yet clear if the poor quality of sleep is a consequence of the presence of several chronic diseases in an individual or whether it leads to an increase in the number of chronic diseases in an individual.…”
Section: Current Smokersupporting
confidence: 93%
“…Likewise, sleep disorders become more frequent in older people [5,6,14]. Risk factors for sleep disorders in old age include gender, being more common in women [7,[15][16][17]; older age [18,19]; lower education [20,21]; loneliness, institutionalization, social isolation [10,16,22,23]; less functionality [23,24]; chronic diseases [25][26][27]; and medication use [5,7,10].…”
Section: Introduction Sleep In Older Agementioning
confidence: 99%
“…Suboptimal sleep, in turn, is responsible for health problems in later life, including physical problems [17,[26][27][28], mental difficulties [7,10,14,22,[28][29][30][31], affectivity imbalance [32], and cognitive impairment [7,10,33,34]. Moreover, poor sleep quality increases the risk of mortality [6,10].…”
Section: Introduction Sleep In Older Agementioning
confidence: 99%
“… 55 Another longitudinal Chinese study revealed participants with poor sleep (sleeping <7 h or >9h) and low physical activity had the highest multimorbidity of chronic diseases compared to other combinations. 56 …”
Section: Discussionmentioning
confidence: 99%